2002
DOI: 10.1890/0012-9658(2002)083[0844:soprbi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship of Permanent-Resident Birds in a Fragmented Forested Landscape

Abstract: Few studies have examined survivorship of animals in forest fragments differing in size, and none has used appropriate mark–recapture analysis techniques taking into account probability of recapture. Using Program MARK, a flexible mark–recapture software package, we estimated annual survival rates of four permanent‐resident woodland bird species over a 5‐yr period in a fragmented landscape. For Carolina Chickadees, White‐breasted Nuthatches, and Downy Woodpeckers, the probability of survival was related to sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 51 publications
3
86
0
3
Order By: Relevance
“…However, not all potential predators pose the same degree of threat to nuthatches. Because small birds like nuthatches may be severely food-limited in the winter as the result of low prey abundance and high energetic demands (22,(30)(31)(32), discriminating among different species of potential predators and mobbing dangerous predators most intensely may help conserve energy. Because they can differentiate among within-category variations of the chick-a-dee alarm calls that contain information about predator risk, nuthatches can selectively mob only the most dangerous predators.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all potential predators pose the same degree of threat to nuthatches. Because small birds like nuthatches may be severely food-limited in the winter as the result of low prey abundance and high energetic demands (22,(30)(31)(32), discriminating among different species of potential predators and mobbing dangerous predators most intensely may help conserve energy. Because they can differentiate among within-category variations of the chick-a-dee alarm calls that contain information about predator risk, nuthatches can selectively mob only the most dangerous predators.…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental food provided at feeding stations can affect distribution, abundance, habitat selection, annual survivorship, sociality, and foraging behavior of birds, especially during winter months (Brittingham and Temple 1988;Desrochers et al 1988;Wilson 2001;Doherty and Grubb 2002;Atchison and Rodewald 2006). Effects of winter resources also can carryover to other seasons and influence the distribution of breeding birds, even though the resource may not be used at that time.…”
Section: Alteration Of Resources and Processes In Urbanizing Landscapesmentioning
confidence: 99%
“…Studies in several parid species have shown enhanced overwinter survival on food-supplemented sites (Jansson et al 1981, Källander 1981, Brittingham and Temple 1988, Doherty and Grubb 2002. Food resources may be particularly important during a limited number of harsh winter days, so perhaps having access to feeders at these critical times improved survival of subordinate birds.…”
Section: Year-dependentmentioning
confidence: 99%